A History of Science $1 (BVolume 3s - Williams, Henry Smith, 1863-1943; Williams, Edward Huntington, 1868-1944 (Salt Lake City, UT : Project Gutenberg, 1999)
"A History of Science $1 (BVolume 3" by Williams and Williams is a scientific publication written during the late 19th century. This volume delves into the modern development of the physical sciences, particularly astronomy, paleontology, geology, meteorology, and their historical significance in shaping our understanding of the natural world. The content covers key figures and concepts that emerged in these fields between the late 17th century and the early 19th century, highlighting advancements that contributed to a more comprehensive view of the universe. The opening of this volume introduces the reader to the transition into modern science, emphasizing the rapid progress made in the 19th century across various disciplines. It begins with a discussion of notable astronomers such as Johannes Hevelius, Edmond Halley, and William Herschel, detailing their contributions to the understanding of celestial bodies, including the discovery of Uranus and advancements in the study of stars and planets. This portion sets the stage for exploring the evolution of fundamental concepts like the conservation of energy, the shape of the Earth, and the nature of comets and meteors, all of which lay the groundwork for modern scientific inquiry. It illustrates how insights gained during this period reshaped perspectives on the universe and humanity's place within it. (This is an automatically generated summary.)s
Volume 3: Modern development of the physical sciences
Release date is 1999-04-01
Produced by Charles Keller, and David Widger
Keywords: Science -- History